Dance Terminology in Digital Media and Online Dance Communities (Eurasian Journal of Humanities and Social Sciences, 2024)
In the contemporary digital era, dance has transcended the physical confines of studios and stages, flourishing within the expansive realm of virtual spaces. This article delves into the pivotal role of dance terminology within digital media and online dance communities, exploring how it shapes communication, learning, and community engagement in these new contexts. The article then contrasts traditional dance terminology with the innovative terms emerging from digital media. It discusses the balance between preserving established terminology and adapting to new digital jargon, illustrating how terms like "TikTok dance challenge" and "viral choreography" reflect contemporary trends while also presenting challenges for consistent understanding.